Simultaneous synthesis and consolidation of nanostructured MgAl2O4-Mg3Al4Ti3O25 composite by pulsed current activated sintering and its mechanical properties - Shon, In-Jin; Doh, Jung-Mann; Yoon, Jin-Kook; Du, Song-Lee (KOREAN ASSOC CRYSTAL GROWTH, INC, 2014)
Nanopowders of Al2O3, TiO2 and MgO were fabricated by high energy ball milling. The simutaneous synthesis and sintering of nanostuctured MgAl2O4-Mg3Al4Ti3O25 composite was investigated by the pulsed current activated sintering process. The advantage of this process is that it allows very quick densification to near theoretical density and inhibition of grain growth. A highly dense nanostructured MgAl2O4-Mg3Al4Ti3O25 composite was produced with the simultaneous application of 80 MPa pressure and a pulsed current of 2000A within one minute. The grain sizes and mechanical properties of MgAl2O4-Mg3Al4Ti3O25 composite sintered at 1150 degrees C were investigated.
Keywords: FABRICATION